Diagnostic Musculoskeletal Ultrasound in the Evaluation of the Glenoid Labrum - Robert C Manske; Chris Wolfe; Phil Page; Michael Voight (International Journal of Sports Physical Therapy, 2026)
The glenoid labrum surrounds the glenoid fossa augmenting its depth and diameter. Along with the glenohumeral capsule and ligaments, it is crucial for shoulder stability. Glenoid labral injuries are very common due to both sports and trauma to the shoulder. When torn the labrum can cause shoulder instability, pain and dysfunction, causing a limitation of function for many essential shoulder movements used in daily living. Lesions of the glenoid labrum require an accurate diagnosis so that decisions about conservative versus surgical treatment can be determined. An accurate diagnosis of labral tears is essential for appropriate treatment planning and optimizing patient outcomes. Diagnostic musculoskeletal ultrasound (MSKUS) has become an imaging modality that is widely used in the assessment of several shoulder pathologies. It offers a portable, real-time, and cost-effective alternative that is gaining traction in rehabilitation and sports medicine settings. MSKUS has emerged as a valuable, non-invasive imaging modality for evaluating glenoid labral tissue. In fact, almost the entire labrum can be visualized using MSKUS. This manuscript will review the utility of MSKUS in evaluating glenoid labrum tissue quality, sonographic techniques, and clinical implications for those in the rehabilitation profession. By integrating MSKUS into clinical practice, providers can improve the accuracy of diagnosis, enhance diagnostic confidence, monitor healing progression, and guide rehabilitation strategies to optimal patient outcomes for those with glenoid labral injuries.